Practices for Wayside Rail Transit Worker Protection - Transportation Research Board; National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2012)
TRB’s Transit Cooperative Research Program (TCRP) Synthesis 95: Practices for Wayside Rail Transit Worker Protection is designed to highlight knowledge, practice, lessons learned, and gaps in information related to wayside rail transit worker protection programs.
Keywords: Transportation and Infrastructure

Shared Use of Railroad Infrastructure with Noncompliant Public Transit Rail Vehicles: A Practitioner's Guide - Transportation Research Board; National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2009)
TRB’s Transit Cooperative Research Program (TCRP) Report 130: Shared Use of Railroad Infrastructure with Noncompliant Public Transit Rail Vehicles: A Practitioner’s Guide examines a business case for the shared use of non-Federal Railroad Administration-compliant public transit rail vehicles (e.g., light rail vehicles) with freight operations and highlights a business model for such shared-use operations. The report also explores potential advantages and disadvantages of shared-use operations and the issues and barriers that can arise in the course of implementation.
Keywords: Transportation and Infrastructure